2019
DOI: 10.3390/pharmaceutics11090437
|View full text |Cite
|
Sign up to set email alerts
|

Arming Filamentous Bacteriophage, a Nature-Made Nanoparticle, for New Vaccine and Immunotherapeutic Strategies

Abstract: The pharmaceutical use of bacteriophages as safe and inexpensive therapeutic tools is collecting renewed interest. The use of lytic phages to fight antibiotic-resistant bacterial strains is pursued in academic and industrial projects and is the object of several clinical trials. On the other hand, filamentous bacteriophages used for the phage display technology can also have diagnostic and therapeutic applications. Filamentous bacteriophages are nature-made nanoparticles useful for their size, the capability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 120 publications
1
34
0
Order By: Relevance
“…For instance, the phage particles were used as nanocarriers in drug delivery, [43][44][45][46][47][48] gene delivery, [49][50][51][52][53] and antigen delivery system in vaccination. 54,55 Taken together, the findings in this investigation indicated that Note: The mean hydrophobicity values and the corresponding standard deviation (SD) are shown for the residues observed in different positions (I-XII) of the displayed peptides at the N-terminus of pIII coat protein for total isolated phages. The statistical analysis of the results demonstrated that the calculated mean hydrophobicity for the each position of peptide sequences is not significantly different from each other (p value > 0.05).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…For instance, the phage particles were used as nanocarriers in drug delivery, [43][44][45][46][47][48] gene delivery, [49][50][51][52][53] and antigen delivery system in vaccination. 54,55 Taken together, the findings in this investigation indicated that Note: The mean hydrophobicity values and the corresponding standard deviation (SD) are shown for the residues observed in different positions (I-XII) of the displayed peptides at the N-terminus of pIII coat protein for total isolated phages. The statistical analysis of the results demonstrated that the calculated mean hydrophobicity for the each position of peptide sequences is not significantly different from each other (p value > 0.05).…”
Section: Resultssupporting
confidence: 55%
“…The broad application of phage for delivery purposes have been also documented by several studies. For instance, the phage particles were used as nanocarriers in drug delivery, 43–48 gene delivery, 49–53 and antigen delivery system in vaccination 54,55 …”
Section: Resultsmentioning
confidence: 99%
“…Filamentous bacteriophages such as M13 are capable of inducing immunity at different levels, as excellently discussed in reviews by De Berardinis’ group [ 68 , 69 ] and others [ 70 ]. Being particulate, they are uptaken and processed by antigen processing cells (APCs), followed by presentation of the deriving peptides by the major histocompatibility complex (MHC) class I and class II molecules.…”
Section: Bacteriophages As Carriers For Cancer Vaccinesmentioning
confidence: 99%
“…Filamentous bacteriophage fd has been proposed as an antigen delivery system for vaccination against tumors, parasites, viruses, and neurodegenerative diseases [11,12,[25][26][27]. Our results suggest that the design of B epitope-specific immunization protocols based on phage fd should take into account the interindividual variability in the strength of the secondary IgG response and the possible disruptive effect of a day 15 booster dose on immunological memory.…”
Section: Discussionmentioning
confidence: 81%